(untitled) (Journal of Faculty of Education, 2022)
هدفت الدراسة إلى تعُرف مدى إمكانية تطبيق التعلُّم الإلكتروني في التدريس الجامعي من وجهة نظر أعضاء هيئة التدريس بجامعة الخرطوم. اتبعت الدراسة المنهج الوصفي، وتكوّنت عينة الدراسة من(199) عضو هيئة تدريس، تم اختيار عينة الدراسة من مجتمع الدراسة بالطريقة العشوائية البسيطة، قام الباحث بإعداد استبانة مكونة من(53) فقرة. وأظهرت النتائج وعي أعضاء هيئة التدريس بجامعة الخرطوم بأهمية التعلُّم الإلكتروني في العمليَّة التعليميَّة ورغبة الأساتذة في مسايرة التطور العلميَّ والتكنولوجي مما يجعلهم يستطيعون استخدامه في التدريس. الأوضاع الاقتصاديّة للكثير من الطلّاب لا تمنكهم من امتلاك الأجهزة اللازمة للتعلُّم الإلكتروني مما يحتٍّم سعي الجامعة لتوفير أجهزة ذكيّة للطلّاب الفقراء. وفي ضوء ما أسفرت عنه الدراسة من نتائج أوصت الدراسة عن حاجة أعضاء هيئة التدريس بجامعة الخرطوم إلى دورات تدريبيَّة حول كيفية تصميم برامج التعلُّم الإلكتروني، وكيفيّة التعامل مع الامتحانات الإلكترونيَّة،كما أوصت بأن تقوم إدارة الجامعة بتجهيز البنية التحتيّة للكليَّات قبل تطبيق التعلُّم الإلكتروني، من حيث تجهيز للفصول الافتراضيَّة، ومعامل الحاسوب، وتجهيز شبكة إنترنت داخليِّة تتمتع بسرعة عالية The study aimed to know the extent of the possibility of employing E-learning in university teaching from the point of view of the staff at Khartoum university. The study followed the descriptive approach.The study sample consisted of(199) faculty members, who were chosen randomly out of population of the study, which was consisted.The researcher build up a questionnaire consisting of(53) paragraphs. The results showed the awareness of the faculty members at the university of Khartoum of the importance of e-learning in the educational process and the desire of teachers to keep pace with the scientific and technological development, which makes them can use it in teaching, and also the economic conditions of many students do not enable them to have the necessary devices for e-learning, which necessitates the university’s endeavor to provide smart devices for the poor students. In light of the results of this study, the faculty members of the university of Khartoum need training courses on how to design e-learning programs, and know how to deal with electronic exams, and also the university administration should prepare the infrastructure of colleges before applying e-learning, from preparing for virtual classes computer labs, and high speed internet access.